Solid suspension and liquid phase mixing in solid-liquid stirred tanks - Sardeshpande, Madhavi V.; Sagi, Aparna R.; Juvekar, Vinay A.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2009)
Stirred tanks are widely used in chemical process industries for catalytic reactions, dissolution of solids, crystallization, and so oil. In designing and optimizing such processes, suspension quality Of Slurry is an important parameter. Suspension quality depends upon complex interactions of impeller generated flow, turbulence, and solid loading. Most of the earlier work on solid suspension focuses Oil identifying critical impeller speed for just suspension of solids (N(js)). In this study, apart from N(js) aspects like cloud height and liquid phase mixing in solid-liquid suspensions were also studied A new way of characterizing solid-liquid suspensions and liquid phase mixing using nonintrusive wall pressure fluctuation measurements has been developed. Systematic experimental data on N(js), cloud height, power consumption, mixing time, and circulation time over a range of solid volume fraction and impeller speeds have been presented here. The results and discussion presented here will have useful implications for designing solid-liquid stirred tanks.

Solid suspension in stirred tanks: UVP measurements and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
Suspension of solids in stirred reactor is widely used for catalytic reactions, dissolution, etc. Quality of solid suspension is an important parameter required for the reliable design, optimum performance, and scale up of the system. Quality of suspension depends on local characteristics of solid velocity and hold up profiles. The present work was focused on investigating quality of solid suspension using ultrasound velocity profiler (UVP) measurements and CFD simulations. The slip velocity measurements carried out with UVP were used to evaluate different drag correlations used in CFD simulations. Results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.
Keywords: CFD; drag coefficient; solid suspension; solid-liquid velocities; UVP

Simulation of settling of solid particles due to sudden impeller stoppage - Sardeshpande, Madhavi V.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2012)
Stirred tank reactors (STRs), which are used in process industries (for a variety of operations, such as catalytic reactions, dissolution of a solid, crystallization, and so on), often involve handling of solid liquid (gas) systems. The solid suspension and the quality of the suspension are key issues in the design and operation of such stirred reactors. Despite extensive experimental work over previous decades, comprehensive understanding and reliable methods to predict the solids suspension and the quality of the suspension are not yet available. Advances in computational fluid dynamics (CFD) and new experimental techniques offer potentially effective ways of understanding solids suspension in stirred tanks. The present work highlights the potential of using transient measurements by way of the dynamic settling of solid particles because of the sudden stoppage of an impeller to evaluate CFD models. Sudden impeller stoppage results in significantly different conditions, in terms of the ratio of particle diameter to Kolomogorov length scale (d(p)/lambda), as well as the solids volume fraction experienced by solid particles. Therefore, experimental data under such sudden impeller stoppage offer a better way to evaluate the influence of prevailing turbulence and solids volume fraction on effective drag and therefore offer a more-stringent test to CFD models than steady-state profiles. Besides facilitating the development of computational models, the experimental and simulation studies of sudden impeller stoppage also provide useful data to gain insight into the behavior of the stirred tank after abrupt impeller stoppage due to sudden power failure.